Management of oral mucositis - da Mota Vasconcelos Brasil Catarina; Sampaio Serpa Marianna; de França Talita Ribeiro Tenório; de Jurema Freire Castro Lisboa (Archive of Oncology, 2012)
Oral mucositis is one of the most common oral complications of cancer treatment. Studies have shown some interventions that reduce the severity of this condition, but there is not a specific treatment proved that really prevents or treats mucositis efficiently. The aim of this paper was to provide a literature review for better understanding of the management of oral mucositis. Pubmed and Scopus were used in order to identify research articles published between 2005 and 2012 in English language. A search term combination that included stomatitis, mucositis, lasers, complimentary therapies, amino acids, antioxidants, vitamins, minerals, plant extracts, and cryotherapy was conducted. A large number of therapeutic strategies to prevent and treat oral mucositis have been shown in studies and growth factors, including palifermin, appear as one of the most innovative drugs used in the management of oral mucositis. Understanding the physiopathological basis of mucositis can lead to the development of target drugs’ therapies. In addition, clinical trials should be conducted in order to determine an efficient protocol of treatment.